Advances in Vascular Medicine - Abraham, David; Handler, Clive; Dashwood, Michael; Coghlan, Gerry (Springer London : Imprint: Springer, 2010)
Understanding the many complex cellular and molecular mechanisms underlying human vascular diseases is essential in improving the management of patients with this clinically important and wide-ranging group of diseases. This is particularly important when considering the extent of this issue across the world. Written by a team of world-renowned authorities, Advances in Vascular Medicine highlights some of the relationships between basic science and clinical medicine, and reviews both research and clinical practice methods and outcomes in vascular biology and pathobiology. It is an authoritative reference for these important topics of vascular biology and includes chapters that explain the clinical issues to the basic scientist as well as providing clinicians with a scientific grounding in vascular diseases. Although there is still much work to be done to advance understanding of vascular disease, the information and insights contained in this book are a vital contribution to the literature, giving scientists and clinicians the opportunity to learn more about this exciting field of biomedicine.